Academic Supervision Strategy in Improving Teachers' Pedagogical and Professional Competence Through Atkinson's Concept - M. Kholilur Rohman; Sutiah Sutiah (Academia Open, 2026)
General Background: Teacher quality determines learning processes and educational development through pedagogical and professional competence. Specific Background: Academic supervision functions to monitor and guide teacher performance but often focuses mainly on administrative evaluation. Knowledge Gap: Supervision practices rarely integrate motivational theory as a structured basis for teacher evaluation and development. Aims: This study examines an academic supervision strategy based on Atkinson’s achievement motivation concept and curriculum evaluation domains. Results: The literature review shows that integrating the structure–process–product framework in supervision encourages intrinsic motivation, openness to feedback, reflective teaching, and innovative instructional practices while supporting systematic evaluation of planning, implementation, and learning outcomes. Novelty: The study proposes a supervision model combining achievement motivation theory with the structure–process–product evaluation framework. Implications: This approach offers an alternative strategy for sustainable teacher professional development and educational quality improvement. Highlights: Structure–process–product evaluation framework supports systematic review of instructional planning, classroom practice, and learning outcomes. Motivation-oriented guidance encourages openness to feedback, reflective teaching, and innovative instructional practice. Continuous mentoring with recognition and moderate challenges supports sustained educator development and learning quality improvement. Keywords: Academic Supervision, Pedagogical Competence, Professional Competence, Atkinson's Concept, Achievement Motivation.